The Three Pillars of Scientific Insight: Understanding the Interconnection of Nature, Culture, and Society through an Islamic - Tahir, Benny Azi Lesmana (International Journal on Advanced Science, Education, and Religion, 2025)
Knowledge in Islam is not merely understood as the product of human rational activity, but also as a means of recognizing Allah SWT and fostering the welfare of humanity. This article discusses the three main pillars of Islamic scientific insight, namely the interconnection between nature, culture, and society as an epistemological unity grounded in the values of tawhid. The study employs philosophical-conceptual and empirical-sociological approaches by examining the ideas of classical and contemporary Muslim thinkers such as Al-Attas, Al-Faruqi, Ibn Khaldun, and M. Amin Abdullah, while relating them to contemporary socio-scientific realities. The findings reveal that, first, nature is perceived as ayat kauniyah (signs of God in the universe) that contain divine knowledge and demand human ecological responsibility. Second, culture functions as a medium for internalizing Islamic values within dynamic and contextual social life. Third, society serves as the arena for the implementation of knowledge through moral, social, and spiritual practices. These three pillars interact in shaping an integrative and civilized Islamic scientific paradigm (science with conscience). Therefore, the integration of nature, culture, and society from an Islamic perspective not only broadens the horizon of Islamic epistemology but also offers solutions to humanitarian crises and the disorientation of values in modern civilization. This holistic Islamic scientific insight is expected to serve as a foundation for the development of knowledge oriented toward justice, public welfare, and cosmic balance.